Interface structure and composition of MoO3/GaAs(0 0 1). (19th March 2018) - Sarkar, Anirban; Ashraf, Tanveer; Grafeneder, Wolfgang; Koch, Reinhold
Abstract: We studied growth, structure, stress, oxidation state as well as surface and interface structure and composition of thermally-evaporated thin MoO3 films on the technologically important III/V-semiconductor substrate GaAs(0 0 1). The MoO3 films grow with Mo in the 6+  oxidation state. The electrical resistance is tunable by the oxygen partial pressure during deposition from transparent insulating to semi-transparant halfmetallic. In the investigated growth temperature range (room temperature to 200 °C) no diffraction spots are detected by x-ray diffraction. However, high resolution transmission electron microscopy reveals the formation of MoO3 nanocrystal grains with diameters of 5–8 nm. At the interface a  ≈3 nm-thick intermediate layer has formed, where the single-crystal lattice of GaAs gradually transforms to the nanocrystalline MoO3 structure. This interpretation is corroborated by our in situ and real-time stress measurements evidencing a two-stage growth process as well as by elemental interface analysis revealing coexistance of Ga, As, Mo, and oxygen in a intermediate layer of 3–4 nm.